Experimental Study on the Compression and Buckling Properties of 3D Printed PLA Materials - Fitria, Laela Nur; Zulaikah, Siti; Djamari, Djati Wibowo; Muflikhun, Muhammad Akhsin; Triawan, Farid (2022)
The rise of advancement in 3D printing technology has made an intricate physical structure easily possible in fabrication. Hence, the mechanical properties and behavior of 3D printed structures are also indispensable to be comprehended and investigated. This work conducted compression tests on 3D printed Polylactic Acid (PLA) to examine buckling properties and behavior. The test was performed on the 10 mm diameter column structure manufactured with the Fused Deposition Method (FDM) and espousing concentric infill pattern. Five variants of column lengths and infill densities were introduced to identify the critical buckling loads. The result of this work is expected to be immensely advantageous to PLA 3D printed structure fabrication and could be applied, for example, to the electric vehicle application that recently also evolved their components by using polymer 3D printing.